2018
DOI: 10.1007/s13679-018-0295-x
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Physical Activity Interventions in Individuals with Binge Eating Disorders

Abstract: Currently, the most effective and well-established psychological treatment for BED is cognitive behavioral therapy (CBT) with a remission rate around 80%. CBT is sometimes combined with pharmacotherapy targeting comorbidities associated with BED, such as obesity and depression. Another avenue of treatment that has been less studied is PA. It has been suggested that PA addresses the underlying mechanisms of BED and, thus, increases treatment efficiency. This systematic review provides additional knowledge conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 64 publications
1
37
1
1
Order By: Relevance
“…The main finding of the current study was that 8-month regular physical activity, along with nutritional education and psychological assistance, significantly improved body composition and physical function in obese or overweight adults suffering from BED. Although changes in weight did not reach statistical significance, the results in the current study are in line with previous research that observed an improvement in physical function and body size and composition [13].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The main finding of the current study was that 8-month regular physical activity, along with nutritional education and psychological assistance, significantly improved body composition and physical function in obese or overweight adults suffering from BED. Although changes in weight did not reach statistical significance, the results in the current study are in line with previous research that observed an improvement in physical function and body size and composition [13].…”
Section: Discussionsupporting
confidence: 89%
“…Although the potential benefits of physical exercise in the general population are well known, according to two previous systematic reviews [13,14], the knowledge about the long-term influence of physical activity in BED is still limited. Comparing our results with those observed in previous studies in BED patients and general population, the non-significant differences in weight and cardiovascular fitness assessed using the 6-min walking test were unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, uncontrolled studies indicate that physical activity reduces binge eating and body weight (Vancampfort et al, ), and increases self‐efficacy in treatment of BED (Vancampfort et al, ). Additionally, a recent systematic review identified beneficial effects from physical activity on treatment of BED (Blanchet et al, ). The weak empirical support for dietary counseling as a single treatment option for BN (Laessle et al, ; Sundgot‐Borgen et al, ) and BED (Hay, ) does not exclude the possibility that such counseling may amplify other treatment approaches such as CBT (Hsu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…While it is well‐documented that exercise is often linked to overvaluation of shape and weight (i.e., core features of anorexia nervosa and bulimia nervosa) for many with EDs, it is also possible that physical activity that is not compulsive or excessive could have psychological and/or physical health benefits for other individuals with EDs. That is, physical activity is a potentially modifiable domain that is thought to facilitate regulation of eating behavior (Joseph, Alonso‐Alonso, Bond, Pascual‐Leone, & Blackburn, ), and a recent review of randomized control trials of physical activity interventions for binge‐eating disorder found that physical activity interventions were associated with reductions in binge eating and depression, and in some cases weight loss (Blanchet et al, ). Thus, for a variety of reasons physical activity has been a domain of particular interest in the study of EDs.…”
Section: Resultsmentioning
confidence: 99%
“…Most assessment studies focused on categorical comparisons of aggregated momentary variables (e.g., average reaction time; Myers et al, ) between ED and control groups, which precludes examination of dynamic, momentary relationships between ED symptoms and relevant physiological, behavioral, and cognitive processes. It was also notable that while there have been several studies of EDs using self‐report measures of physical activity (e.g., see Blanchet et al, ), which were excluded from the review, there is a dearth of research examining objective physical activity levels in daily life and especially in binge‐type EDs. In addition, many studies were excluded that applied objective monitoring techniques in controlled settings, particularly inpatient and day hospital programs.…”
Section: Discussionmentioning
confidence: 99%